(untitled) (PIONIR: JURNAL PENDIDIKAN, 2022)
Education at SMA Negeri 1 Tapaktuan is still faced with 4 obstacles in improving the quality of education, namely: (1) limited number of teachers and TU; (2) the uneven distribution of teachers; (3) lack of teacher professionalism; and (4) various facilities for teaching and learning activities that do not meet the standards, in particular the lack of procurement of Indonesian language textbooks that are relevant to the needs of students, schools, and regions in accordance with the demands of K-13. This research was conducted with the objectives of: (1) formulating the need for teaching materials according to teachers and students; (2) developing prototypes into Indonesian language and literature teaching materials with a thematic approach in high school; (3) knowing the effectiveness of the developed teaching materials; and (4) determine the feasibility of teaching materials for Indonesian language and literature with a thematic approach in high school. The research and development (R&D) method is used in this research to produce teaching materials. The results obtained: 1) the need for teaching materials according to teachers and students, paying attention to: (a) the language context for various language purposes, (b) keeping up with the times, (c) according to K13 by raising themes around students, (d) relevance between teacher and student teaching materials; (f) assignments/practices can activate students, (g) the material attracts students’ interest, is clear, and easy to understand, and (h) is relatively ready to use in minimal school facilities; 2) developing prototypes into Indonesian language and literature teaching materials with a thematic approach in high school is done by: (a) compiling syllabus, lesson plans, teacher teaching materials and student teaching materials, (b) authentic materials and assignments/exercises developed thematically and situational and develop intellectual and affective insight, and (c) the assessment process is carried out by classroom assessment; 3) the results of the effectiveness test with a non-independent t-test showed that the thematic teaching materials were effective; and 4) the results of the feasibility of developing Indonesian language and literature teaching materials with a thematic approach are stated to be good with components of content/material feasibility assessment 77.92%, linguistics 73.40%, material presentation 77.92%, and graphics 70.